Perbandingan Indeks Keanekaragaman Serangga Di Wilayah Ekosistem Hutan Penyangga Taman Nasional Gunung Leuser Bukit Lawang - Gunarno Gunarno (Balai Diklat Keagamaan Medan, 2021)
This study aims to determine the diversity index and the comparison of insect diversity index in Gunung Leuser Bukit Lawang National Park in the Buffer ecosystem area. The research method uses a quantitative descriptive approach. The population in this study were all animals classified as insects (Insecta). The samples used were insects in the buffer forest area with 3 standpoints (lines). The data analysis technique uses the Shannon–Wiener diversity index. The results showed that the insect with the highest significance index (INP) from the three lines (without stands, rubber stands, and cocoa stands) was Macrotermes gilvus, namely 91.71 (rubber tree stands), 87.54 (cocoa tree stands), and 57. 42 (without stands). The insect diversity index H' using (Shannon-Wiener Index) from the three lines without stands (-2), rubber stands (-1), and brown stands (-1) were “low”. The low diversity index of the buffer forest is because the buffer forest in Bukit Lawang is a homogeneous forest.